Journal of Therapeutic Ultrasound - Gedroyc, Wladyslaw; Foley, Jessica; Muratore, Robert
Journal of Therapeutic Ultrasound encompasses all aspects of therapeutic ultrasound, namely, the stimulus, inhibition, or modification of tissue function or structure via insonification. This open access journal focuses on translational and clinical research, helping to accelerate the adoption of therapeutic ultrasound as a clinical tool.